EI24 binds to IGF1R, enhancing glucose homeostasis and fostering healthy aging in male mice - Kim, You-Min; Lee, Seung Eon; Song, Yaechan; Nam, Tae Wook; Lee, Jaehoon; Seong, Je Kyung; Namkung, Wan; Lee, Han-Woong (Frontiers in Aging, 2025)
IntroductionThe etoposide-induced 2.4 kb transcript (EI24) plays a crucial role in autophagy, facilitating the clearance of damaged proteins and organelles to maintain cellular homeostasis. While autophagy is widely recognized for its beneficial effects on healthy aging, the effects of EI24 overexpression remain unclear.MethodsWe analyzed the interaction of EI24 with the insulin-like growth factor 1 receptor (IGF1R), a key molecule associated with aging. Ei24 transgenic (TG) mice were generated to assess the effects of Ei24 overexpression on aging, glucose homeostasis, and resistance to streptozotocin (STZ)-induced diabetes.ResultsEI24 was found to bind to IGF1R, specifically engaging with its transmembrane (TM) domain near the cytoplasmic membrane, and suppress its phosphorylation. Male Ei24 TG mice exhibited signs of healthier aging, with reduced aging markers in the kidney, liver, and pancreas. Moreover, Ei24 overexpression enhanced glucose uptake, likely due to increased Glut4 expression in muscle tissue. Ei24 TG mice also demonstrated resistance to high-dose STZ-induced diabetes.ConclusionThese findings suggest that Ei24 overexpression contributes to improved glucose regulation and healthier aging across multiple organs. By interacting with IGF1R, EI24 may provide a novel mechanism for promoting metabolic and age-related health.